Serum copeptin predicts atrial fibrillation recurrence and is associated with increased all-cause mortality - Martin Ihnatko; Zora Lazúrová; Ivana Jochmanová; Ľudmila Ihnatková; Ivica Lazúrová (Frontiers in Cardiovascular Medicine, 2026)
Introduction Copeptin, a stable surrogate marker of arginine vasopressin, reflects neurohumoral activation and hemodynamic stress. Its prognostic value in heart failure is established, but its role in atrial fibrillation (AF) recurrence and mortality remains unclear. This study aimed to compare copeptin concentrations in patients with AF and controls, evaluate biochemical and echocardiographic associations, and assess copeptin associations with 12-month AF recurrence and all-cause mortality. Methods This prospective observational study included 100 hospitalized patients with AF and 50 controls in sinus rhythm. Participants underwent clinical evaluation, echocardiography, biochemical testing, and measurement of copeptin, N-terminal pro-B-type natriuretic peptide (NT-proBNP), and high-sensitivity cardiac troponin T (hsTnT). AF recurrence was evaluated in 62 patients after sinus-rhythm restoration; mortality was assessed in all 100 patients over a 12-month follow-up period. Results Median copeptin concentration was higher in patients with AF than in controls, 14.52 (6.98–36.83) versus 4.10 (2.70–6.88) pmol/L ( p < 0.0001), and remained higher after adjustment for age and sex (adjusted geometric mean ratio, 2.995; 95% CI, 2.040–4.398; p < 0.0001). In patients with AF, copeptin correlated positively with C-reactive protein (ρ = 0.4862), hsTnT (ρ = 0.4904), NT-proBNP (ρ = 0.3458), left atrial volume index (LAVi; ρ = 0.2598), and left ventricular mass index (ρ = 0.2252), and inversely with estimated glomerular filtration rate (ρ = −0.3231) and tricuspid annular plane systolic excursion (ρ = −0.2277; all p < 0.05). Each 10-pmol/L copeptin increase was independently associated with 61% higher AF recurrence odds after adjustment for age, LAVi, and left ventricular ejection fraction (adjusted OR, 1.61; 95% CI, 1.01–2.56). Copeptin showed modest discrimination for AF recurrence (AUC, 0.674; 95% CI, 0.526–0.821); the 11.68-pmol/L cut-off yielded 63.33% sensitivity and 75.00% specificity. Median copeptin concentration was higher in non-survivors than survivors, 35.35 (10.35–56.82) versus 12.20 (6.54–29.43) pmol/L ( p = 0.0051). Discussion In hospitalized patients with AF, copeptin is elevated and associated with cardiac biomarkers, inflammation, and structural and functional echocardiographic abnormalities. Higher copeptin independently predicts AF recurrence after sinus-rhythm restoration and is associated with 12-month all-cause mortality, supporting its potential for risk stratification and prognostic assessment.